054 An adult case of acute cerebellitis as a manifestation of Mycoplasma Pneumoniae infection. (23rd August 2021) - Ji, Amanda; Roizman, Michael; Swayne, Andrew
Abstract : Introduction: Acute cerebellitis is exceptionally rare in adults often preceded by systemic viral or bacterial infections. We present a case of acute cerebellitis following otherwise asymptomatic Mycoplasma Pneumoniae infection. Case Descriptions: A 40-year-old man presented with a three-day history of acute onset of dizziness, vomiting and headache which was initially diagnosed and managed as vestibular neuritis. He was discharged and four days later represented with slurred speech and difficulty walking. On examination, he was alert, had an ataxic gait, dysarthria and bilateral hypermetric saccades. CSF studies showed an elevated leukocyte count of 152X10 6 /L with 100% mononuclear cells and a mildly elevated protein level of 0.7g/L with normal glucose. Other CSF analysis including a multiplex PCR panel for a variety of viral, bacterial and fungal pathogens, cytology, flow cytometry, antineuronal and encephalitis antibody tests were negative. MRI showed features consistent with acute cerebellitis including subtle diffuse cerebellar hyperintense signal on T2 and FLAIR sequences. Serological testing showed the presence of Mycoplasma Pneumoniae IgM and IgG. A diagnosis of acute cerebellitis was made, and the patient received supportive care and made a complete neurological recovery after 10 days. A repeat MRI one month later showed imaging resolution and he remained asymptomatic at clinic follow-up. Conclusion: This case describes an adult with cerebellitis most likely secondary to Mycoplasma Pneumoniae infection with other causes excluded on extensive investigation. Although rare, acute cerebellitis should be considered as a part of the differential diagnosis of acute vertigo particularly in the presence of cerebellar signs.